Uma aventura marítima no Livro de Linhagens do Conde D. Pedro = A maritime adventure in Count D. Pedro's Lineage Book - Miranda, José Carlos Ribeiro (2019)
Count Dom Pedro's Livro de Linhagens is well-known for its epiclegendary narratives that have contributed very much to its diffusion nowadays. Among these narratives stands out the one related to the invasion of the Douro River by an armada of Gascons which, after a hard fight against the Moors that dominated the region, settled in Baião, and became one of the most important founding lineages of the kingdom of Portugal. But this narrative may be no more than the visible face of a largescale invasion of the Portuguese territory that took place between 1014 and 1016, involving Vikings and other people with different origins, which marked the future of what would become, a century later, the kingdom of Portugal.